2006
DOI: 10.1177/001979390605900307
|View full text |Cite
|
Sign up to set email alerts
|

Internal Promotion versus External Recruitment in Industrial Plants in Spain

Abstract: respectively. This study began when Alberto Bayo was a visiting researcher at the Departament d' Economia de l' Empresa of the Universitat Autònoma de Barcelona. The authors would like to thank Vicente Salas, Emilio Huerta and two anonymous referees for their comments, and the BBVA Foundation and the BEC2001-2552-C03-01 project for their financial assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 62 publications
1
34
1
5
Order By: Relevance
“…Empirical evidence on the influence of specific industrial sectors on the internal hiring decision is provided by an analysis of a sample of Spanish industrial plants surveyed in 1997 [13]. The surveyed group was a representative sample of more than 6,000 Spanish manufacturing plants with 50 or more workers in a dozen sectors.…”
Section: Influence Of Industrial Sector and Job Title On Internal Hiringmentioning
confidence: 99%
“…Empirical evidence on the influence of specific industrial sectors on the internal hiring decision is provided by an analysis of a sample of Spanish industrial plants surveyed in 1997 [13]. The surveyed group was a representative sample of more than 6,000 Spanish manufacturing plants with 50 or more workers in a dozen sectors.…”
Section: Influence Of Industrial Sector and Job Title On Internal Hiringmentioning
confidence: 99%
“…This theoretical …nd-ing is supported by the empirical study of Bayo-Moriones and Ortín-Ángel (2006), who analyze the recruitment and promotion decisions of 653 Spanish …rms. They …nd that the degree of competition has a positive and statistically highly signi…cant impact on the use of internal promotions.…”
Section: Introductionmentioning
confidence: 83%
“…However, selecting the right person for a leadership position is paramount to organizational success, and internal promotion is a routine practice in cultivating the next generation of leaders. 12 This practice has been thoroughly supported by studies indicating that internally cultivated leaders promoted from within the organization generate higher rates of organizational performance than their externally recruited counterparts. 3,13 Consideration for internal promotion is supported by other studies that have shown that organizations that place an emphasis on in-house promotion report higher financial returns than those organizations that do not.…”
Section: Internal Versus External Leadership Successionmentioning
confidence: 94%